Unravelling the origin of in-cage vibrations in a La50Al15Ni35 metallic glass. (November 2021) - Qiu, K.K.; Wang, X.D.; Xu, T.D.; Liu, J.; Cao, Q.P.; Zhang, D.X.; Jiang, J.Z.
Abstract: The structural origin of β -relaxation is still an open issue in glassy materials. Focusing on the as-cast and annealed La50 Al15 Ni35 metallic glasses (MGs), we demonstrate that the local vibration of Ni atoms contributes more to the β -relaxation in both samples through synchrotron X-ray measurements and theoretical calculations. It is found that besides the free volume decreases, the chemical constitution around mobile Ni atoms in Ni-centered polyhedra tends to transform from Al-free to Al/Ni-containing after annealing, which suppress the local vibration of central Ni atoms, thus leading to the unpronounced β -relaxation event. Moreover, we observe that the atomic mobility of Ni atoms more depends on their local polyhedral geometry and chemical constitution than the content of surrounding free volume. Our work paves a way to better understand the origin of β -relaxation in MGs and other glassy materials from their local atomic environments. Graphical abstract: Image 1 Highlights: The kinetics of as-cast and annealed La50 Al15 Ni35 samples were studied systematically. Free volume is simulated quantitatively and not an only factor for atomic motion and the β -relaxation. Chemical constitution and local packing structure play a significant role in the mobility of atoms.